R&S e Competitività internazionale nell'industria manifatturiera europea: un'analisi settoriale - Barbara Pantiglioni; Enrico Santarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
– The purpose is to explain the relation between the dynamics of R&D expenditures and that of exports in the four largest EU countries: France, Germany, Italy, and United Kingdom. Estimation of a fixed effects (Least Squares Dummy Variable) panel model for manufacturing as a whole and for fourteen (two digit) industries in manufacturing over the 1981-1992 period points out a positive and significant relation between variation in the share of R&D by each of the relevant countries on total R&D by all OECD countries and variation in the share of export by each of the relevant countries on total exports by OECD countries. In particular, this relation is stronger in Motor vehicles & equipment, Chemicals & pharmaceuticals, Mechanical engineering, Food, beverages & tobacco, paper & printing, whereas it turns out to be of scant significance for Textiles, clothing & footwear. In the light of these findings, further support is forthcoming to the hypothesis that the competitive advantage/disadvantage of nations is strongly connected to their innovative capability.
Keywords: 330